Megaureter - Steve J. Hodges; David Werle; Gordon McLorie; Anthony Atala (The Scientific World Journal)
Almost one-quarter of the children referred to a pediatric urologist for obstructive uropathy suffer from an obstructive megaureter. However, not all megaureters are due to obstruction, as some may be the result of reflux and many simply represent a slightly skewed stage of development that can result in a normal urinary tract if observed. As the use of fetal ultrasonography has expanded, the majority of children with megaureters are now diagnosed early in their development, and physicians are faced with the complex task of distinguishing which children need medical intervention and which do not. The surgical treatments of megaureter are well established, relatively simple, and effective if performed in the correct candidates. Therefore, research efforts in this field have recently focused on improving our ability to diagnose clinically relevant obstructive uropathy and examining the developmental causes of megaureter, and how this disorder may be prevented.